Calculation method for the axial load-bearing capacity of steel pipe-to-sleeve grouted connections. (3rd January 2022) - Wu, Liwei; Guo, Xueyuan; Chen, Haibin; Liu, Junyang; Su, Youpo
Highlights: Grouting material reaching ultimate tensile strain as the limit state. Propose the theoretical model of steel pipe-to-sleeve grouted connections. The three-way constitutive relationship of the grout is considered. Abstract: The existing axial load-bearing capacity calculation method for the steel pipe-to-sleeve grouted connections is introduced. It is proposed that by considering the tensile strain of a grouting material along the inner cyclic direction of the sleeve reaching its ultimate tensile strain as the limit state, the limit load-bearing capacity calculation model of the steel pipe-to-sleeve grouted connections is established via:1.) the deformation coordination relationship among the cyclic strain of the sleeve, steel pipe and the grout; 2.) the overall static equilibrium of the grout; and 3.) the three-way constitutive relationship of the grout. The calculation model has a wide application range and strong applicability, In addition, the proposed model is used to calculate the axial load-bearing capacity of 82 sets of steel pipe-to-sleeve grouted connection specimens in the literature, and the calculated values agree well with the experimental values.